PENGARUHÃÂ SUASANAÃÂ KEGIATANÃÂ BELAJARÃÂ MENGAJARÃÂ TERHADAPÃÂ PRESTASIÃÂ BELAJARÃÂ PADAÃÂ MATAÃÂ DIKLATÃÂ MOTORÃÂ BENSINÃÂ ÃÂ ÃÂ - AnggriawanÃƒÂ‚Ã‚Â , DimasÃƒÂ‚Ã‚Â BayuÃƒÂ‚Ã‚Â ; BudiyonoÃƒÂ‚Ã‚Â , Aris; RusiyantoÃƒÂ‚Ã‚Â , - (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2008)
Penelitian ini bertujuan untuk mengetahui: (1) suasana kegiatan ÃÂ belajar mengajar mata ÃÂ diklat MotorÃÂ Bensin ÃÂ dan ÃÂ hasil ÃÂ belajar ÃÂ siswa, ÃÂ dan ÃÂ (2) mengetahui ÃÂ pengaruh ÃÂ suasana ÃÂ kegiatan ÃÂ belajar mengajar ÃÂ terhadap ÃÂ hasilÃÂ belajar ÃÂ siswa. ÃÂ Populasi ÃÂ dalam ÃÂ penelitian ÃÂ adalah ÃÂ 106 ÃÂ siswa ÃÂ dari ÃÂ tiga ÃÂ kelas ÃÂ XI ÃÂ program ÃÂ keahlian ÃÂ Teknik MekanikÃÂ Otomotif SMK Palapa ÃÂ Jatibarang Semarang ÃÂ tahun pemelajaran 2009/2010. Sampel penelitian ÃÂ sebanyak 25 ÃÂ siswaÃÂ tiap ÃÂ kelas ÃÂ diambil ÃÂ dengan ÃÂ teknik ÃÂ purposive ÃÂ random ÃÂ sampling. ÃÂ Alat ÃÂ pengumpulan ÃÂ data ÃÂ yang ÃÂ digunakan ÃÂ yaituÃÂ dokumentasi ÃÂ dan ÃÂ angket. ÃÂ Data ÃÂ dianalisis ÃÂ dengan ÃÂ deskripsi ÃÂ dan ÃÂ regresi ÃÂ linier ÃÂ sederhana. ÃÂ Analisis ÃÂ deskripsiÃÂ menyatakan bahwa suasana kegiatan belajar mengajar dan hasil belajar masuk pada kategori tinggi. Hasil analisisÃÂ regresi menunjukkan bahwa terdapat pengaruh suasana kegiatan belajar mengajar terhadap hasil belajar siswa.Kata kunci: pengaruh suasana KBM, hasil belajarÃÂ This research is aimed to find out: (1) the atmosphere of teaching and learning activity in Gasoline MotorÃÂ training ÃÂ subject and ÃÂ studentsÃ¢â¬â¢ ÃÂ study ÃÂ results, and ÃÂ (2) ÃÂ the effect of ÃÂ the atmosphere ÃÂ toward ÃÂ studentsÃ¢â¬â¢ ÃÂ study ÃÂ results.ÃÂ Population ÃÂ of ÃÂ this ÃÂ research ÃÂ was ÃÂ 106 ÃÂ students ÃÂ from ÃÂ three ÃÂ classes ÃÂ of ÃÂ Automotive ÃÂ Mechanical ÃÂ Engineering ÃÂ skillÃÂ program at SMK Palapa Jatibarang Semarang year 2009/2010. Meanwhile, the sample of it was about 25 studentsÃÂ taken ÃÂ from ÃÂ each ÃÂ class ÃÂ using ÃÂ purposive ÃÂ random ÃÂ sampling ÃÂ technique. ÃÂ Data ÃÂ collecting ÃÂ instruments ÃÂ used ÃÂ wereÃÂ documentation ÃÂ and ÃÂ questionnaire. ÃÂ The ÃÂ data ÃÂ was ÃÂ analyzed ÃÂ using ÃÂ description ÃÂ and ÃÂ simple ÃÂ linier ÃÂ regression.ÃÂ Descriptive analysis states ÃÂ that ÃÂ the atmosphere of ÃÂ teaching and ÃÂ learning activity and study result come ÃÂ into highÃÂ category. On ÃÂ the ÃÂ other hand, ÃÂ regression ÃÂ analysis ÃÂ indicates ÃÂ that ÃÂ the ÃÂ atmosphere of ÃÂ teaching ÃÂ and ÃÂ learning ÃÂ activityÃÂ affects studentsÃ¢â¬â¢ study results.Keywords: the effect of Teaching and Learning Activity (KBM), study result